2010
DOI: 10.1021/ja100571h
|View full text |Cite
|
Sign up to set email alerts
|

Truncated Octahedral Pt3Ni Oxygen Reduction Reaction Electrocatalysts

Abstract: This communication describes the preparation of carbon-supported truncated-octahedral Pt(3)Ni nanoparticle catalysts for the oxygen reduction reaction. Besides the composition, size, and shape controls, this work develops a new butylamine-based surface treatment approach for removing the long-alkane-chain capping agents used in the solution-phase synthesis. These Pt(3)Ni catalysts can have an area-specific activity as high as 850 muA/cm(2)(Pt) at 0.9 V, which is approximately 4 times better than the commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
468
3
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(494 citation statements)
references
References 25 publications
17
468
3
6
Order By: Relevance
“…In contrast, PtCo/C-80 with a thicker Pt skin was able to sustain its high activity despite a slightly lower initial activity. Octahedral PtNi nanoparticles which expose a predominance of extremely high activity PtNi(111) show impressive activity in RDE, 19,[28][29][30][31][32][33] yet when measured in an MEA, only a small fraction of the activity was realized. 1 The very thin Pt skin and a high transition metal dissolution rate are believed to be the predominant causes of its instability.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, PtCo/C-80 with a thicker Pt skin was able to sustain its high activity despite a slightly lower initial activity. Octahedral PtNi nanoparticles which expose a predominance of extremely high activity PtNi(111) show impressive activity in RDE, 19,[28][29][30][31][32][33] yet when measured in an MEA, only a small fraction of the activity was realized. 1 The very thin Pt skin and a high transition metal dissolution rate are believed to be the predominant causes of its instability.…”
Section: Resultsmentioning
confidence: 99%
“…288 The population of the truncated-octahedral shape depended on the types and amounts of reducing and capping agents used. Wu et al 288 believed that the two types of long-alkane-chain amines resulted in different portions of truncated octahedral: when hexadecylamine was used as a capping agent, a small portion of cubes was observed (Figure 15a,b) while the use of dodecylamine led to 100% truncated-octahedral nanocrystals of Pt 3 Ni, as shown in Figure 14c. In addition to the use of different alkane chain lengths, a combination of strong (boranetert-butylamine complex, TBAB) and mild (hexadecanediol) reducing agents was used to effectively adjust the nucleation and growth rate.…”
Section: 303mentioning
confidence: 99%
“…248,341 Wu et al 288 reported truncated-octahedral Pt 3 Ni (t,o-Pt 3 Ni) catalysts with a particle size of 5−7 nm that had a dominant exposure of {111} facets. Three sets of Pt 3 Ni nanocrystals were generated with various mixtures of truncated octahedral (exposing both {111} and {100} facets) and cubes (exposing only {100} facets).…”
Section: Effect Of Particle Shape On Orr Activitymentioning
confidence: 99%
“…Improvements can be made to catalysts by forming non-equilibrium morphologies. 14,38,[49][50][51][52][53] Very recent results by Chen et al 13 have shown unprecedented capabilities of Pt x Ni ''nanoframes'' to catalyze oxygen reduction.…”
Section: Introductionmentioning
confidence: 99%